Clinical characteristics of acute respiratory distress syndrome survived patients at a tertiary hospital in Jakarta (Medical Journal of Indonesia, 2017)
Background: While a good deal of research on characteristic the different characteristics between surviving and dying patient with ARDS has been conducted globally, such research is scarce in developing countries. This study aimed to obtain clinical profile of ARDS survivors during hospitalization. Methods: This was a prospective, observational study conducted at a tertiary hospital in Jakarta from October 2015 to April 2016. Primary data was collected from ARDS patients based on Berlin Definition admitted to emergency room, ICU, HCU, ICCU, and all other wards. The patients were followed until they discharged. We only included survivors on the analysis. Descriptive analysis was done using SPSS 21.0. Results: A total of 43 patients were survived during study period. The majority were below 65 years of age (69.8%) and were male (53.5%). ARDS was mainly mild in severity (62.8%) and early onset (55.8%). Sepsis was the most common causes of ARDS (97.7%). Most of the patients had comorbidities (74.4%). Majority of the patients had APACHE II score <20 (77.3%) with mean 15.6±4.8. The mean of albumin was 2.9±0.6 and the median of procalcitonin was 3 (0.1-252.3). Conclusion: The clinical profile of ARDS survivors in our study were mostly similar with other studies conducted in developed and other developing countries.